Experimental evidence on the effects of home computers on academic achievement among schoolchildren - Robert W. Fairlie; Jonathan Robinson (University of California, Economics Department, 2013)
Computers are an important part of modern education, yet many schoolchildren lack access to a computer at home. We test whether this impedes educational achievement by conducting the largest-ever field experiment that randomly provides free home computers to students. Although computer ownership and use increased substantially, we find no effects on any educational outcomes, including grades, test scores, credits earned, attendance and disciplinary actions. Our estimates are precise enough to rule out even modestly-sized positive or negative impacts. The estimated null effect is consistent with survey evidence showing no change in homework time or other intermediate inputs in education.
Keywords: I24; 330; education; technology; digital divide; experiment; computers